The Necessity of Educational Content for Indonesian Society Through YouTube Channels - ZUBAIDI, Abdul Khakim Mahfud (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:This study aims to analyze the factors contributing to the Indonesian public's low preference for educational content on YouTube, including audience preferences and psychosocial factors influencing media consumption patterns. Additionally, the study examines the potential outcomes of increased exposure to educational content, particularly in terms of knowledge improvement, behavioral changes, and its broader contribution to human capital development in Indonesia.Methodology:This research employs a qualitative descriptive approach and a case study method to examine India’s legal framework in combating illegal wildlife trafficking.Findings:This study finds that the role of educational content on YouTube is crucial in enhancing public literacy in Indonesia. The analysis shows that while educational content has the potential to improve knowledge and awareness significantly, many people still prefer entertainment-based videos over informative ones. However, challenges such as low digital literacy, lack of interest, and algorithm-driven content preferences hinder its reach. The findings emphasize the urgent need for content creators to innovate in delivering educational material while policymakers and institutions should support initiatives that promote informative content on digital platforms.Implication:The implications of this study extend to both practical and academic domains. Practically, the findings serve as a valuable reference for content creators in designing engaging and educational videos that align with audience preferences, thereby enhancing the effectiveness and reach of educational content on YouTube. Academically, this research contributes to the body of knowledge in communication studies, sociology, arts, and other relevant disciplines by providing empirical insights into audience behavior and the role of digital media in public education.